Personalized prompt generator and ai chatbot for dietary and exercise planning: a controlled investigation of adherence and physical fitness over 12 weeks in older Malaysian adults / Qautsar Malini Khairolnezam ... [et al.]. - Khairolnezam, Qautsar Malini; Mohd Dan, Azwa Suraya; Sazali, Razif; Md Yusoff, Yusandra; Zulqarnain, Muhammad; Haziq, Amrun; Linoby, Adam (Universiti Teknologi MARA, Negeri Sembilan, 2025)
This study evaluates the effectiveness of a novel prompt generator (NExGEN) and AI chatbot (ChatGPT) intervention in improving exercise and dietary adherence, and physical fitness among older adults over three months. By comparing pre- and post-intervention outcomes, it addresses gaps in understanding AI-driven personalized strategies for sustained adherence and health improvements in elderly populations.